2010
DOI: 10.3945/jn.109.113357
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Requirement of Healthy, School-Aged Indian Children Determined by the Indicator Amino Acid Oxidation Technique

Abstract: We recently reported the lysine requirement of school-aged children living in Canada consuming a mixed diet to be 35 mg.kg(-1).d(-1). Because the majority of children in the world live on cereal-based diets in developing countries, we measured the daily lysine requirement in healthy children living in India and consuming a mostly cereal-based diet. Our objective in this study was to determine the lysine requirement in healthy, school-aged children in the developing world by using the indicator amino acid oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…Therefore, tyrosine should be present in relative excess to sensitively partition the carboxyl carbon of phenylalanine between the incorporation into protein or oxidation. The amounts of phenylalanine and tyrosine in the current study were comparable to earlier childhood amino acid IAAO-requirement studies (18)(19)(20)(21)(22) and were shown to sensitively display a breakpoint in phenylalanine oxidation in response to test diet intakes.…”
Section: Tracer Protocolsupporting
confidence: 54%
See 2 more Smart Citations
“…Therefore, tyrosine should be present in relative excess to sensitively partition the carboxyl carbon of phenylalanine between the incorporation into protein or oxidation. The amounts of phenylalanine and tyrosine in the current study were comparable to earlier childhood amino acid IAAO-requirement studies (18)(19)(20)(21)(22) and were shown to sensitively display a breakpoint in phenylalanine oxidation in response to test diet intakes.…”
Section: Tracer Protocolsupporting
confidence: 54%
“…Our studies of amino acid requirements in adult humans and children yielded requirement estimates for lysine (13,21,22), total sulfur amino acids and minimum methionine (19,20,41,42), and total branched chain amino acids (14,18) that were not different between age groups. We hypothesized that the similar results suggested that maintenance needs are similar in adults and children (6-10 y old) who are slow growing.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It had been hypothesized that these populations may be able to adapt and thrive on a lower lysine intake than that needed in the developed world. To test this question, the lysine needs of school-aged children in Toronto, Canada, and in Bangalore, India, were measured and shown to be identical (Pillai et al 2010). Moreover, the lysine requirements in moderately malnourished Indian children increased by 20% because of gut parasite infection (Pillai et al 2015).…”
Section: Protein and Amino Acid Requirementsmentioning
confidence: 99%
“…Therefore, employing the nitrogen balance method, the metabolic demand for protein cannot be assessed in patients with a widely varying metabolic demand. The indicator amino acid oxidation (IAAO) method was originally employed to study amino acid requirements in pigs ( 8 ), and thereafter it has been widely used for studies on pigs ( 9-11 ) and humans (12)(13)(14)(15)(16)(17). Since the IAAO method does not require prior dietary adaptation ( 18 ) to each of the varying protein intake levels, it could be available when an assessment of the metabolic demand for protein is required for post-operative patients or patients with injuries or infections.…”
mentioning
confidence: 99%